2014
DOI: 10.1016/j.bbamem.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Actin Cytoskeleton of Host Macrophages is Essential for Leishmania donovani Infection

Abstract: Visceral leishmaniasis is a vector-borne disease caused by an obligate intracellular protozoan parasite Leishmania donovani. The molecular mechanism involved in internalization of Leishmania is poorly understood. The entry of Leishmania involves interaction with the plasma membrane of host cells. We have previously demonstrated the requirement of host membrane cholesterol in the binding and internalization of L. donovani into macrophages. In the present work, we explored the role of the host actin cytoskeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 48 publications
1
46
0
1
Order By: Relevance
“…In support of these results, Rodríguez et al showed that plasma membrane cholesterol is necessary for the entry of Leishmania chagasi into host macrophages [23]. In addition, we have recently shown that destabilization of the actin cytoskeleton of macrophages results in reduction in the entry of Leishmania donovani into host cells, due to a possible cross-talk between membrane cholesterol and the actin cytoskeleton [24]. This observation is relevant in light of the emerging relationship between membrane cholesterol and the actin cytoskeleton [25-28; P. Sarkar, G.A.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 68%
See 3 more Smart Citations
“…In support of these results, Rodríguez et al showed that plasma membrane cholesterol is necessary for the entry of Leishmania chagasi into host macrophages [23]. In addition, we have recently shown that destabilization of the actin cytoskeleton of macrophages results in reduction in the entry of Leishmania donovani into host cells, due to a possible cross-talk between membrane cholesterol and the actin cytoskeleton [24]. This observation is relevant in light of the emerging relationship between membrane cholesterol and the actin cytoskeleton [25-28; P. Sarkar, G.A.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 68%
“…Viability of macrophages upon treatment with lovastatin or MβCD-cholesterol complex was assessed using MTT assay as described earlier [24,37].…”
Section: Mtt Viability Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane cholesterol is often found to be distributed in a nonrandom fashion in domains (or pools) in biological and model membranes [50][51][52][53]. These domains are envisaged to be crucial since various cellular processes such as membrane sorting and trafficking [54], signal transduction [55], and the entry of pathogens [56][57][58] have been attributed to these types of domains. As mentioned earlier, the role of cholesterol in the function and organization of membrane proteins and receptors constitutes an emerging and exciting area of research [36,[41][42][43][44].…”
Section: Cholesterol: a Lipid Intimately Associated With Gpcrsmentioning
confidence: 99%